Research Registries: A Tool to Advance Understanding of Rare Neuro-Ophthalmic Diseases. Issue 3 (September 2016) - Blankshain, Kimberly D.; Moss, Heather E.
Abstract : Background: Medical research registries (MRR) are organized systems used to collect, store, and analyze patient information. They are important tools for medical research with particular application to the study of rare diseases, including those seen in neuro-ophthalmic practice. Evidence Acquisition: Evidence for this review was gathered from the writers' experiences creating a comprehensive neuro-ophthalmology registry and review of the literature. Results: MRR are typically observational and prospective databases of de-identified patient information. The structure is flexible and can accommodate a focus on specific diseases or treatments, surveillance of patient populations, physician quality improvement, or recruitment for future studies. They are particularly useful for the study of rare diseases. They can be integrated into the hierarchy of medical research at many levels provided their construction is well organized and they have several key characteristics including an easily manipulated database, comprehensive information on carefully selected patients, and comply with human subjects regulations. MRR pertinent to neuro-ophthalmology include the University of Illinois at Chicago neuro-ophthalmology registry, Susac Syndrome Registry, Intracranial Hypertension Registry, and larger-scale patient outcome registries being developed by professional societies. Conclusion: MRR have a variety of forms and applications. With careful planning and clear goals, they are flexible and powerful research tools that can support multiple different study designs, and this can provide the potential to advance understanding and care of neuro-ophthalmic diseases.